The VP1 subunit of JC polyomavirus recapitulates early events in viral trafficking and is a novel tool to study polyomavirus entry - Nelson, Christian D.S. (2012)
JC polyomavirus (JCV) is an important human pathogen that causes the fatal demyelinating disease progressive multifocal leukoencephalopathy (PML). In this study we further delineate the early events of JCV entry in human glial cells and demonstrate that a pentameric subunit of the viral capsid is able to recapitulate early events in viral trafficking. We show that JCV traffics to the endoplasmic reticulum (ER) by 6 h post infection, and that VP1 pentamers arrive at the ER with similar kinetics. Further, this JCV localization to the ER is critical for infection, as treatment of cells with agents that prevent ER trafficking, ER function, or ER quality control reduce JCV infectivity. These pentamers represent a new tool to study polyomavirus entry, and will be particularly useful in studying recently identified polyomaviruses that are difficult to propagate.